2007
DOI: 10.1007/s10973-006-7733-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gypsum using TMDSC

Abstract: Gypsum is a dihydrated calcium sulfate, with the composition of CaSO 4 ⋅2H 2 O, with large application interest in ceramic industry, odontology, sulfuric acid production, cement, paints, etc. During calcination, a phase transformation is observed associated to the loss of water, leading to the formation of gypsum or anhydrite, which may present different phases. The identification of the phases is not so easy since their infrared spectra and their X-ray diffraction patterns are quite similar. Thus, in this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Its use in construction dates back to the Neolithic age, and it still represents a commodity material in the building industry with an annual worldwide production of about 150 million tons . Consequently, the formation, , processing, and mechanical properties of gypsum and its related compounds, anhydrite (CaSO 4 ) and bassanite (CaSO 4 ·0.5H 2 O), have been studied in great detail. Using infrared spectroscopy, the water dynamics inside gypsum crystals can be studied, indicating that the crystal water in bulk gypsum is constrained to a single conformation .…”
Section: Introductionmentioning
confidence: 99%
“…Its use in construction dates back to the Neolithic age, and it still represents a commodity material in the building industry with an annual worldwide production of about 150 million tons . Consequently, the formation, , processing, and mechanical properties of gypsum and its related compounds, anhydrite (CaSO 4 ) and bassanite (CaSO 4 ·0.5H 2 O), have been studied in great detail. Using infrared spectroscopy, the water dynamics inside gypsum crystals can be studied, indicating that the crystal water in bulk gypsum is constrained to a single conformation .…”
Section: Introductionmentioning
confidence: 99%
“…In materials such as silica, researchers have identified that the phase transformation of the materials due to the increase in the contact stresses is the primary reason for pop-in events in the loading curves [ 23 , 25 ]. However, for porous materials (such as shales, plaster, or other cementitious materials), phase transformations due to temperature changes [ 44 , 45 ] and hence the pop-in events in such materials can be attributed to the possible dislocation networks and cracking during the indentation loading.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to different phases of calcium sulfate, crystal water content is one of the key parameters to assess their phase transformation and crystallization . Hence, TG analysis was performed and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%